Web hacking : become a professional web pentester (Packt Publishing, 2019)
"This course contains everything to start working as a web pentester. You will learn about exploitation techniques, hacking tools, methodologies, and the whole process of security assessments. It is absolutely hands-on, you will do all the attacks in your own penetration testing environment using the provided applications. The targets are real open-source software. You will have to work hard but in the end, you will be able to do web security assessments on your own as a real ethical hacker. My name is Geri and I am the instructor of this course about web application hacking. If you are interested in hacking and IT security, then this is the perfect place to start. You might be a developer, an IT administrator, or basically anybody with an IT background. With this training, you will get everything you need to start working as a professional web penetration tester."--Resource description page